2005
DOI: 10.1139/f05-011
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the hypothalamo-pituitary-interrenal axis in 1+ yellow perch (Perca flavescens) chronically exposed to metals in the environment

Abstract: Although it has been reported that adult yellow perch (Perca flavescens) chronically exposed to metals in the environment exhibit endocrine impairment characterized by blunted cortisol secretion, little is known about the vulnerability of early life stages. Young-of-the-year (YOY) and 1+ yellow perch were captured, subjected to a standardized stress test or adrenocorticotropic-hormone stimulation in lakes situated along a contamination gradient of Cd, Cu, and Zn in the mining region of Abitibi, Quebec. For the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 49 publications
(71 reference statements)
1
9
0
1
Order By: Relevance
“…DDT: Benguira et al, 2002), and metals (Gagnon et al, 2006;Gravel et al, 2005;Hontela, 1998;Laflamme et al, 2000;Norris et al, 1999). In particular, effects on the stress axis similar to those observed in the present study have recently been reported for rainbow trout, Oncorhynchus mykiss, exposed to municipal waste water effluent for 14 days (Ings et al, 2011a,b).…”
Section: Consistency Of These Findings With Previous Studiessupporting
confidence: 89%
“…DDT: Benguira et al, 2002), and metals (Gagnon et al, 2006;Gravel et al, 2005;Hontela, 1998;Laflamme et al, 2000;Norris et al, 1999). In particular, effects on the stress axis similar to those observed in the present study have recently been reported for rainbow trout, Oncorhynchus mykiss, exposed to municipal waste water effluent for 14 days (Ings et al, 2011a,b).…”
Section: Consistency Of These Findings With Previous Studiessupporting
confidence: 89%
“…Complementary biochemical measurements were carried out on adult (4+), juvenile (1+), and young of the year (YOY) yellow perch (Levesque et al 2002(Levesque et al , 2003Gravel et al 2005). Blood, liver, and muscle samples were collected and analyzed for hormones (cortisol, triiodothyronine T3, thyroxine T4) and various biochemical parameters (glucose, glycogen, lipids).…”
Section: Endocrine and Metabolic Statusmentioning
confidence: 99%
“…Previous studies examining wild yellow perch inhabiting metal-contaminated lakes have reported impairments in cortisol stress response, intermediary metabolism, seasonal storage of energy reserves and aerobic capacities in the more contaminated fish (Levesque et al 2002;Rajotte and Couture 2002;Couture and Kumar 2003;Gravel et al 2005;Couture et al 2008a). These investigations were carried out in two areas on the Canadian Precambrian Shield that have been subjected to metal emissions from smelters for over 80 years, the Rouyn-Noranda (Quebec) and the Sudbury (Ontario) regions.…”
Section: Introductionmentioning
confidence: 98%